Method of Chronoionometric Determination of Concentrations of Fluorine, Nitrate, Ammonium in Drinking Water - Surovtsev, I.V.; Galimov, S.K.; Galimova, V.M.; Sarkisova, M.V. (Cybernetics and computer engineering, 2021)
The purpose of the paper is to apply the developed method of chronoionometry to measure the concentrations of fluoride, nitrate, ammonium in drinking water and to assess the accuracy of measuring concentrations. Results. Methods for detection the concentrations of fluorine, nitrates, ammonium in drinking water were obtained and tests were performed in model aqueous solutions using the device of inversion chronopotentiometry "Analyzer SCP", which testify to the compliance of measurement errors with metrological normative values. Мета статті — застосувати розроблений метод хроноіонометрії для вимірювання концентрацій фтору, нітратів, амонію у питній воді та оцінити точність вимірювання концентрацій. Результати. Розроблено способи виявлення концентрацій фтору, нітратів, амонію у питній воді та проведено тестування в модельних водних розчинах з використанням приладу інверсійної хронопотенціометрії «Аналізатор ІХП», які свідчать про відповідність похибок вимірювання концентрацій метрологічним нормативним значенням.